Design of a Small Renewable Resource Model based on the Stirling Engine with Alpha and Beta Configurations - Faisal Zahari; Muhammad Murtadha Othman; Ismail Musirin; Amirul Asyraf Mohd Kamaruzaman; Nur Ashida Salim; Bibi Norasiqin Sheikh Rahimullah (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the conceptual design of Stirling engine based Alpha and Beta configurations. The performances of Stirling engine based Beta configuration will be expounded elaborately in the discussion. The Stirling engines are durable in its operation that requires less maintenance cost.  The methodology for both configurations consists of thermodynamic formulation of Stirling Cycle, Schmidt theory and few composition of flywheel and Ross-Yoke dimension. Customarily, the Stirling engine based Beta configuration will operate during the occurrence of low and high temperature differences emanating from any type of waste heat energy. A straightforward analysis on the performance of Stirling engine based Beta configuration has been performed corresponding to the temperature variation of cooling agent. The results have shown that the temperature variation of cooling agent has a direct effect on the performances of Stirling engine in terms of its speed, voltage and output power.